Estimation of the parameters of traveling ionospheric disturbances using a chirp-ionosondes network - A.A. Kolchev; E.Yu. Zykov; F.I. Vybornov; A.G. Chernov; V.V. Shumaev (Учёные записки Казанского университета: Серия Физико-математические науки)
In this article, the results of our observations of traveling ionospheric disturbances are discussed using the data from a network of chirp stations for oblique ionospheric sounding in December 2019. All observations were made with the same type of chirp stations located in the village of Vasilsursk, as well as in the cities of Yoshkar-Ola, Kazan, and Nizhny Novgorod. The stations formed six synchronous sounding paths with a length from 120 to 320 km. The amplitude-frequency and distance-frequency characteristics were registered per minute by the stations of oblique chirp sounding.